Integrated approach of revised universal soil loss equation (RUSLE) and geographical information system (GIS) for soil loss risk assessment in Gola watershed, Uttarakhand - DUTTA, TITHI; KUMAR, PANKAJ; VISHWAKARMA, DINESH KUMAR; KUMAR, ROHITASHW; S.H., DHEERAJ KUMAR (Journal of Soil and Water Conservation, 2024)
The Revised Universal Soil Loss Equation (RUSLE) is the most extensively used empirical model for erosion prediction and monitoring the conservation method by understanding the driving forces behind soil erosion, we can more easily identify erosion-prone areas within a landscape to address the problem strategically. Remote sensing techniques and geographic information systems (GIS) have become essential tools, particularly for measuring erosion on a wider scale, because it has the benefit of requiring less data and covering a larger area with less resources. The RUSLE is utilized in GIS in this study to determine how much soil is lost each year in the Gola watershed, which is part of the Ganga basin. This type of information can be very useful in determining where erosion control measures should be implemented first. The rate of soil erosion was computed as a function of topography, soil texture, land use/land cover, rainfall erosivity, and cover and practice management in the watershed using the Revised Universal Soil Loss Equation (RUSLE), remote sensing imagery, and GIS. The estimated rainfall erosivity, soil erodibility, slope length and steepness, cover management and practice management factors range from 679.21MJ/mm ha-1 hr-1year-1 to 1255.84 MJ/mm ha-1 hr-1/year, 0.020281 t ha-1 MJ-1 mm-1, 0.316 to 260.3192, 0 to 0.2 and 0 to 1, respectively. Priority soil and water conservation measures must be implemented to the severity of soil loss. To reduce soil loss in farmed parts of the state, agricultural practices should be diversified to include farm forestry, agro-horticulture, and/or agro-forestry. Such conservation programmes assist in mitigating accelerated soil erosion, restoring fragile ecosystems, and creating employment opportunities.